(untitled) (Globalization and Business, 2018)
The article views environmental protection issues in the energy sector of Georgia. Trends of developing energy complex are discussed and assessed envisaging ecological requirements. It is indicated that energy complex is the most polluting one among the fields of material production. Focus in made on ecological problems of the land, including cultivable ones, water, climate and other fields. The Georgian experience is presented in respect with meeting these challenges. At the end, views are given for improving the situation. Points to be stressed are: Rational production and usage for energy resources, creation of energy recourse-conserving, low waste or no waste environmentally clean technologies, reduction of emissions, and thermal gases polluting an environment, decrease of harmful action of industrial and other waste and waste utilization; Construction and reconstruction of systems of protection of environment, including increase of rates of filtration and neutralization of natural substances in the exhaust gases, waste water, cleaning of ground polluted and damaged during construction and operation of energy facilities, and also usage of industrial waste as secondary raw material; Provision of economic incentives of rational use of casing-head gases, suppression of practice of their burning in their torches (first of all at the experience of creation of economically favorable conditions for use of such gases); Introduction of environmentally clean technologies of coal burning in thermal power stations and other enterprises, as a condition of coal use prospects; Improvement of coal fuel quality (including its enrichment, processing, bracketing etc.); Usage of mine methane; Growth of production of high-quality engine fuels appropriate to the European standards, improved for conformity with the requirements of the advanced legal base for polluting substances and exhaust gases emitted as a result of oil products combustion; Development and realization of the programs of minimization of environmental damage caused by construction and functioning of hydroelectric power stations; Organization of works of certification of environmentprotection technologies and means; Organization of experts training working in a sphere of an environmental protection.